2017
DOI: 10.20944/preprints201702.0033.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Analysis of Thermal Runaway in 18650 Cylindrical Li-Ion Cells Using an Accelerating Rate Calorimeter

Abstract: Abstract:In this work commercial 18650 lithium-ion cells with LiMn2O4, LiFePO4 and Li(Ni0.33Mn0.33Co0.33)O2 cathodes were exposed to external heating in an Accelerating Rate Calorimeter (es-ARC, THT Company) to investigate the thermal behavior under abuse conditions. New procedures for measuring external and internal pressure change of cells were developed. The external pressure was measured utilizing a gas-tight cylinder inside the calorimeter chamber in order to detect venting of the cells. For internal pres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The onset and the peak temperatures change depending on the chemistry adopted for the manufacturing of the lithium-ion cell, as well as on the cell design and the size of the considered battery pack. Table IV resumes the most important thermal characteristics of the different lithium-ion technologies available on the market [14,15]. It is worth considering that, even if the conditions for a thermal runaway are not reached, a number of less severe conditions can still occur in case of abuse operating conditions: the vented gases (produced by a damaged electrolyte) are flammable and in case of ignition can generate a fire; even if not ignited, they are corrosive and can impact on the surrounding items (corrosion, chemical burns to users, etc.…”
Section: Fig 4 Temperature Trend During Heating Test and Subsequent mentioning
confidence: 99%
“…The onset and the peak temperatures change depending on the chemistry adopted for the manufacturing of the lithium-ion cell, as well as on the cell design and the size of the considered battery pack. Table IV resumes the most important thermal characteristics of the different lithium-ion technologies available on the market [14,15]. It is worth considering that, even if the conditions for a thermal runaway are not reached, a number of less severe conditions can still occur in case of abuse operating conditions: the vented gases (produced by a damaged electrolyte) are flammable and in case of ignition can generate a fire; even if not ignited, they are corrosive and can impact on the surrounding items (corrosion, chemical burns to users, etc.…”
Section: Fig 4 Temperature Trend During Heating Test and Subsequent mentioning
confidence: 99%
“…They confirmed that the cell with LFP as the cathode exhibits better thermal stability, whereas the cell with NMC as the cathode shows terrible temperature tolerance (Lei et al, 2017). Moreover, the difference in maximum temperature between LFP and NMC is more than 400 C (Lei et al, 2017). Furthermore, the toxic gaseous emission and the combustion hazards can result in serious secondary disasters for battery systems, which attract much attention from researchers.…”
Section: Introductionmentioning
confidence: 96%
“…On that basis, Feng et al pioneered the improved extended-volume accelerating rate calorimetry (EV-ARC) to study TR of large format LIBs and summarized three critical temperatures T 1 , T 2 , and T 3 which represent the onset temperature of self-heating, the TR triggering temperature, and the maximum temperature during TR process, respectively (Feng et al, 2014(Feng et al, , 2019. To compare the thermal behaviors of LIBs built by different material systems, Lei et al used (NMC 111), respectively (Lei et al, 2017). They confirmed that the cell with LFP as the cathode exhibits better thermal stability, whereas the cell with NMC as the cathode shows terrible temperature tolerance (Lei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the booming development of the electric vehicles (EVs) in recent years, lithium iron phosphate (LiFePO 4 ) power batteries have occupied a large market share due to their high‐rate discharge capability, stable charge‐discharge platform, low self‐discharge properties, and long cycle life . Unfortunately, as the power sources of the EVs, there remain formidable challenges of the sharp capacity fading and safety problems during the repeated high‐rate and/or long‐time discharge processes, especially the most common ones caused by the overcharge of the batteries . After overcharge, not only severe and sharp capacity degradation is inevitable, but also safety issues, such as thermal runaway, or even flatulence and explosion will occur in extreme cases .…”
Section: Introductionmentioning
confidence: 99%